Dependencia emocional y depresión en hombres con pareja de la región de Ayacucho, Perú - Galindo Mejía, Katherine Isabel (2024)
The aim of this article is to determine the relationship between emotional dependency and depression in men with partners who are beneficiaries of a health or community service. Using a mixed methodology (qualitative and quantitative), with a correlational and causal design, 150 men from the Ayacucho region were assessed using the Beck Depression Inventory (BDI-II) and the Emotional Dependency Questionnaire by Lemos and Londoño (EDQ). The study employs a non-experimental, ex post facto, and relational design. The results show high levels of depressive symptoms and moderate levels of emotional dependency. Depression is significantly related to separation anxiety, emotional expression towards the partner, fear of loneliness, and the expression of boundaries. Fear of loneliness and occupation are the main predictors of depression, explaining 29% of the variance. This study confirms the relationship between emotional dependency and depression in men with partners in Ayacucho, highlighting occupation and fear of loneliness as key predictors, affecting their masculinity and emotions, a topic that is under-researched in the Andes.